Penerapan Problem Based Learning dalam Meningkatkan Literasi Argumentatif Siswa SMP pada Materi Pidato (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to apply the Problem Based Learning (PBL) model based on the Culturally Responsive Teaching (CRT) approach to improve junior high school students' argumentative literacy in speech text material. The study was conducted on grade VIII-E students of SMP Negeri 7 Banjarmasin with a descriptive qualitative approach through documentation and observation of teaching modules, teacher reports, and learning evaluation results. The results of the study indicate that the application of PBL syntax - starting from problem orientation through contextual speech texts, group work with LKPD, presentation of discussion results, to evaluation using applications such as Kahoot is able to improve students' abilities in analyzing text structures, compiling arguments, and expressing opinions logically and critically. The CRT approach strengthens the relevance of the material to the students' cultural background, thus encouraging active involvement and deeper understanding. The application of PBL and CRT has proven effective in forming critical thinking skills and improving the quality of Indonesian language learning that is more contextual and meaningful.